Gastric pouch obstruction in a bariatric patient caused by the ingestion of cocaine packets: a case report - Vitoretti, Matheus; Mota, David de Freitas; Silva, Gabriel Thiago da; Caliman, Gabriella Catharno; Andrate, Izabella Dias Munis de; Carneiro, Ana Clara Warkentin Araujo; Pádua, Priscila; Migliore, Renato; Schlenstein , Henrique Perobelli; Gentile, João Kleber de Almeida (Brazilian Journal of Case Reports, 2023)
The term "Body Packing" refers to individuals who carry intra-abdominal foreign objects containing illicit drugs that have been ingested to conceal them for smuggling purposes. With the increasing rates of international smuggling, drug transportation across borders has been constantly evolving among traffickers. Once introduced into the body, it becomes a matter of significant medical concern, as it can cause bowel obstruction, perforation, peritonitis, or intoxication. We present a case of a female, 44 years old, with a history of Fobi-Capella bariatric surgery, who was admitted to an Emergency Department for intractable vomiting, excessive drooling, and confirmed ingestion of 25 cocaine packages. The abdominal CT revealed multiple foreign bodies in the gastroenteroanastomosis topography, gastric pouch, and small bowel. Exploratory laparotomy with gastrostomy, enterotomy, and colotomy was performed. A second approach with intraoperative endoscopy was conducted to remove the remaining packages that were revealed by CT. This case report provides information about body packers’ clinical condition, diagnosis, and treatment, to assist surgeons and clinicians with similar cases.